2014
DOI: 10.1007/s00784-014-1245-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis for the assessment of trabecular peri-implant alveolar bone using panoramic radiographs

Abstract: Trabecular bone around successful dental implants exhibits lower fractal dimension values 6 months after prosthodontic loading and displays stable bony microstructure at 12 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 41 publications
2
56
0
3
Order By: Relevance
“…[2][3][4][14][15][16][17] Considerable research has also been carried out to evaluate the mineral density of bones in various parts of the body, especially in patients with osteoporosis, and to examine the use of radiomorphometric studies in the diagnosis of osteoporosis. [18][19][20] In many of these studies, various parameters, which can be merged under the names of mandibular indices and mandibular cortical bone, were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][14][15][16][17] Considerable research has also been carried out to evaluate the mineral density of bones in various parts of the body, especially in patients with osteoporosis, and to examine the use of radiomorphometric studies in the diagnosis of osteoporosis. [18][19][20] In many of these studies, various parameters, which can be merged under the names of mandibular indices and mandibular cortical bone, were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…FA has been used for image analysis of trabecular bone structure of patients with osteoporosis, hyperparathyroidism and implant planning. 13,[22][23][24][25][26][27][28] In a radiography study on the relationship between periodontal disease and bone destruction, it was reported that the destructive effects of periodontal pathology on trabecular bone can be successfully evaluated with FA. Researchers have stated that even small trabecular destructive changes in the early stages of the disease can be determined by FA before the effects of periodontal pathology are clearly emerged.…”
Section: Discussionmentioning
confidence: 99%
“…De Molon et al [11] evaluated for the first time the pattern of bone remodeling in sinus lifting in human biopsies using autogenous bone graft by means of FD and histological analysis. Zeytinoğlu et al [12] reported that trabecular bone around successful dental implants exhibits lower FD values 6 months after prosthodontic loading and displays stable bony microstructure at the 12-month follow-up point. Bianciardi et al [13] found that parameters based on a combination of ultrasonic examination and fractal analysis on radiographic images may add useful structural information regarding the patient's skeleton using noninvasive procedures.…”
Section: Discussionmentioning
confidence: 99%